Professional Competence of a Lawyer - Mudryk, Alla; Kykhtuik, Oksana (Psychological Prospects Journal, 2020)
The article analyzes the main approaches within which the professional competence of a lawyer is studied. The Phenomena of «Competence», «professional competence» are described. Based on the theoretical and methodological analysis of the scientific literature, the main characteristics of legal activity are generalized. The Psychological peculiarities of a Lawyer’s activity are considered, the System of personal qualities of a lawyer that determine the efficiency of professional activity is determined. Peculiarities of formation of professional competence of a specialist are outlined. The Components of the lawyer’s personality are considered, the set of which is aimed at improving the professional activity. It is noted that the professional competence of a lawyer is characterized by the formation of a holistic set of knowledge, skills, psychological qualities, professional opportunities. It is noted that a professionally competent person is a special specification of the category «Personality». The Personality of the specialist is a system of certain psychological properties and traits that are necessary for the effective performance of professional activities; professionally competent person characterizes a person as a specialist who has sufficient professional knowledge, skills, abilities, professional interest, professional interest and abilities, professional approach and professional attitude to their work and is able to effectively implement professional activities and anticipate its consequences; professionally competent person has the appropriate professional knowledge and skills (which determine the effectiveness of professional activities) and a set of professionally important qualities (set of psychological qualities of personality that determine the success of training and effective performance of professional activities), which together allow a person to realize himself as a professional. The definition of professional competence of the specialist of legal sphere of activity is offered, its structure where the basic constituent components are: general cultural competence is opened; personal-motivational competence; practical activity competence; special; professional and legal competence; personal (personality) competence; communicative competence; psychological competence; socio-psychological competence; social-perceptual competence; autocompetence.